2016
DOI: 10.1016/j.artres.2016.10.154
|View full text |Cite
|
Sign up to set email alerts
|

Application of non-invasive central aortic pressure assessment in clinical trials: Clinical experience and value

Abstract: Pressure measured with a cuff and sphygmomanometer in the brachial artery is accepted as an important predictor of future cardiovascular (CV) events. However, recent clinical evidence suggests that central aortic pressure (CAP) provides additional information for assessing CV risk than brachial blood pressure (BrBP). Central hemodynamics can now be noninvasively assessed with a number of devices, however, the methodology employed to measure CAP, in order to better identify the patients at higher CV risk in cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 91 publications
0
5
0
3
Order By: Relevance
“…Peripheral systolic blood pressure is the most commonly used measure of circulatory function and cardiovascular risk. However, a significant predictive benefit has been observed when measuring central (aortic) blood pressure (cBP) (Agabiti-Rosei and Muiesan, 2015 ; Williams et al, 2018 ) and it has been suggested that cBP should be a better indicator of risk (Agabiti-Rosei et al, 2007 ; Avolio et al, 2009 ; Sharman et al, 2013 ; McEniery et al, 2014 ; Agabiti-Rosei and Muiesan, 2015 ; Williams et al, 2017 ) since it is more representative of the load exerted on major organs (Herbert et al, 2014 ; Agabiti-Rosei and Muiesan, 2015 ; Williams et al, 2017 ). For instance, elevation of cBP induces coronary arteriosclerosis which in turn can lead to adverse events such as stenosis and myocardial infarction (Agabiti-Rosei et al, 2007 ) and causes chronic kidney disease that can advance to end-stage renal disease (Safar et al, 2002 ; Ohno et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral systolic blood pressure is the most commonly used measure of circulatory function and cardiovascular risk. However, a significant predictive benefit has been observed when measuring central (aortic) blood pressure (cBP) (Agabiti-Rosei and Muiesan, 2015 ; Williams et al, 2018 ) and it has been suggested that cBP should be a better indicator of risk (Agabiti-Rosei et al, 2007 ; Avolio et al, 2009 ; Sharman et al, 2013 ; McEniery et al, 2014 ; Agabiti-Rosei and Muiesan, 2015 ; Williams et al, 2017 ) since it is more representative of the load exerted on major organs (Herbert et al, 2014 ; Agabiti-Rosei and Muiesan, 2015 ; Williams et al, 2017 ). For instance, elevation of cBP induces coronary arteriosclerosis which in turn can lead to adverse events such as stenosis and myocardial infarction (Agabiti-Rosei et al, 2007 ) and causes chronic kidney disease that can advance to end-stage renal disease (Safar et al, 2002 ; Ohno et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the effect of cardiovascular parameters on PP could improve cBP assessment from non-invasive pBP measurements; specially central PP (cPP) assessment which has been shown to be of greater predictive value for cardiovascular outcomes than brachial PP (Safar et al, 2002;Williams et al, 2006). Large PP values have been associated with male sex (Segers et al, 2009;Herbert et al, 2014), higher heart rate (Wilkinson et al, 2002), height (Asmar et al, 1997;Camacho FIGURE 1 | Central and peripheral pressure waveforms. Central pulse pressure, cPP, is mainly determined by the blood flow ejected by the ventricle into the aorta, Q in , and the total arterial compliance, C T (Vennin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Da mesma maneira, como descrito a seguir, estudos prospectivos observacionais têm demonstrado o valor preditivo de parâmetros hemodinâmicos centrais para eventos CV na população geral, nos idosos e nos pacientes com doença coronária e com doença renal crônica (DRC). 228 …”
Section: Valor Prognóstico Das Medidas Derivadas Dos Parâmetros Centraisunclassified
“…Recent clinical studies have shown that central (aortic) blood pressure (cBP) is a better cardiovascular risk indicator than brachial blood pressure (bBP) ( 1 – 4 ), since cBP is more representative of the load exerted on major organs ( 1 , 5 ). Regardless of gender or disease, cBPs in subjects with similar brachial systolic blood pressure (SBP) may differ by up to 33mmHg, resulting in “a significant overlap of central SBP scores between brachial SBP risk groups” ( 6 ).…”
Section: Introductionmentioning
confidence: 99%